1968 und die Avantgarde: Politisch-ästhetische Wechselwirkungen in der westlichen Welt - Sanio, Sabine (Sinzig Studio, 2008)
this study focuses on some of the presuppositions of what changed the arts and lifestyles in the last third of the 20th century. It traces the (strongly French-influenced) idea of "revolutionising everyday life", the impulsive concepts of the Surrealists and Dadaists as well as the migration of "situationist" strategies. She praises everything that came across the ocean with John Cage or Nam June Paik in terms of de-hierarchisation and the idea of democratisation in art. Also parallel movements in the European avant-garde to developments in the USA - especially the connections between musical innovations (exemplary: Mauricio Kagel and Dieter Schnebel) and those in the visual arts. Regardless of the current occasion, a central field of modernist aesthetics is outlined - and the engagement in it. Finally, a counterpoint: a conversation with the Viennese literary and cultural scholar Helmut Lethen, one of the activists of the student movement in West Berlin. Lethen takes a sceptical look at the 'avant-gardes' - those of music as well as the political ones.
'Fantasia contrappuntistica' - Ein Gespräch mit Helmut Lethen; Vom Ton der Väter zum Sound der Söhne
Keywords: Avant-garde; Esthetics; Music philosophy and esthetics; Politics